The effects of age and gender and elite levels on perceptual–cognitive skills of adolescent badminton athletes - Wu, Kuo-Cheng; Lee, Yu-Lung; Chen, Shiau-Cheng (Frontiers in Psychology, 2024)
Introduction This study aimed to examine perceptual-cognitive skills across age, gender and elite levels of badminton adolescent athletes. Methods A total of 57 badminton athletes divided into junior high school athletes (age = 13.36 ± 1.14 years, females = 22, males = 11) and senior high school athletes (age = 16.25 ± 0.84 years, females = 11, males = 13) were evaluated using a cognitive component skills approach. Elite levels were classified as semi-elite (n = 29, score = 3.23) and competitive elite (n = 28, score = 5.84) levels. Each group completed a cognitive test, including an evaluation of their capacity for Corsi block-tapping (CCT) and spatial priming tasks (SPT). Results No gender effects were found in the perceptual skills of the adolescent players, and the age effect was consistent across gender. For the elite levels, the perceptual-cognitive skills of SPT of reaction time was performed equally in the groups of semi-elite and competitive players, however, in the CCT Span of working-memory (WM), competitive-elite players outperformed semi-elite players. Conclusion We found that perceptual-cognitive skills of WM play crucial roles in the open-skill sports of badminton. Thus, when developing advanced skills to higher elite levels in adolescent players, perceptual-cognitive skills should be considered.